1997
DOI: 10.2307/2965737
|View full text |Cite
|
Sign up to set email alerts
|

The New Statistical Analysis of Data

Abstract: The new statistical analysis of data / T. W. Anderson, Jeremy D. Finn. p. em.Includes bibliographical references and index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 0 publications
0
34
0
3
Order By: Relevance
“…vective activity in the SACZ. The Mann-Whitney U test (e.g., Anderson and Finn 1996) with a 0.05 significance level indicated that the two samples of factor-1 scores correspond to independent populations. Conversely, factor-2 score distributions cannot be considered distinct with the same level of significance.…”
Section: A Interpretation Of Factor Analysis and Convective Patternsmentioning
confidence: 99%
“…vective activity in the SACZ. The Mann-Whitney U test (e.g., Anderson and Finn 1996) with a 0.05 significance level indicated that the two samples of factor-1 scores correspond to independent populations. Conversely, factor-2 score distributions cannot be considered distinct with the same level of significance.…”
Section: A Interpretation Of Factor Analysis and Convective Patternsmentioning
confidence: 99%
“…The second step in the procedure consists of estimating the parameters of the identified probability distribution candidates. For this, it relies on well-known estimation procedure such as the Maximum Likelihood and the Moment Matching estimates [3,19]. Finally, once the candidate distributions parameters are estimated, they are evaluated using goodness-of-fit tests to decide if they represent a good fit to the input data and to select the best fit.…”
Section: Distribution Fittingmentioning
confidence: 99%
“…To estimate the parameters of mixture models, i.e. the parameters ω of the sub-distributions D i and the selection distribution W , one may use classical estimation techniques such as the likelihood estimate or the moment matching estimate [3,19]. However, in this setting such techniques often fail to perform the estimation.…”
Section: Learning and Fitting Techniquesmentioning
confidence: 99%
See 2 more Smart Citations